Differences In The Growth Rate Of Tomato Plants ( Solanum Lycopersicum L) When Applying NPK Fertilizer And Compost Fertilizer - Rofita, Dewi; Wangung, Yuliana; Foriman, Selestinus; Rendo, Gordianus; Abu, Yulius Frit; Mita, Karmelita Gresiana (UNIVERSITAS PAKUAN, 2024)
This research was conducted in Cancar, Ruteng District, Manggarai Regency in the Wae Bahi 1 Farmer Group starting from September-November 2023. This research aims to determine the difference in the growth rate of tomato plants when applied with NPK fertilizer and compost fertilizer. This research is a type of experimental research with 4 levels of treatment, namely: P1: 2 g NPK + 200 g compost/planting hole, P2: 4 g NPK + 200 g compost/planting hole, P3: 6 g NPK + 200 g compost/planting hole, P4: 8 g NPK + 200 g compost/planting hole. The parameters observed in this research were plant height, stem diameter, number of leaves and leaf length. The observation data was then analyzed using Excel. The results of the research show that the combination of 6 g NPK fertilizer and 200 g compost fertilizer is the best combination in increasing the growth of tomato plants (more efficiently) regarding the parameters of plant height, stem diameter, leaf length and number of leaves when observed 2 to 5 weeks after planting (MST)